Fracture toughness of single grains and polycrystalline Li7La3Zr2O12 electrolyte material based on a pillar splitting method. Issue 8 (July 2020) - Nonemacher, Juliane Franciele; Arinicheva, Yulia; Yan, Gang; Finsterbusch, Martin; Krüger, Manja; Malzbender, Jürgen
Highlights: The mechanical properties of LLZO with two different grain sizes were investigated. Large grain sample has higher E and H compared to small grain sample. Pillar splitting method was adopted to determine the fracture toughness. K IC obtained via pillar splitting agrees well with that via Vickers indentation. Grain boundaries show positive effect on K IC whereas negative on conductivity. Abstract: In the present study an advanced pillar splitting method is used to determine the fracture toughness of a garnet-type Li7 La3 Zr2 O12 (LLZO) electrolyte. The obtained results are compared to data derived on the basis of conventional Vickers indentation. Furthermore, potential micro-pillar size effects are investigated. The estimated fracture toughness values for single grains and polycrystalline LLZO material obtained via both methods are in good agreement, yielding ∼ 1 MPa m 0.5, hence the data indicate that LLZO exhibits relatively low fracture toughness and has a brittle behavior.